A professional learning community as a vehicle for the development of writing pedagogy: a case study of a teacher professional development project - Joseph, Marion Theodora (My University, 2017)
This thesis investigates the potential of an externally initiated and facilitated professional learning community (PLC) to influence and possibly change teachers’ beliefs and practices with regard to the teaching of writing in South African senior phase English home language classrooms. The main research question is: What factors enable and / or constrain the development of a PLC which has as its focus the teaching of writing. Questions related to the main question are (1) What is enabling or constraining about the contexts in which teachers work in public schools? (2) What, if any, impact do teachers’ life histories and current identities have on their take up of professional development opportunities in a PLC which focused on the teaching of writing? (3) In the context of South African public education, to what extent is a PLC a suitable vehicle for developing teachers’ understanding of and enactment of writing pedagogies? I chose to undertake an action research project and participated in the process of establishing PLCs as both a researcher and a facilitator. The main sources of the data analysed are transcribed audio-recordings of meetings with teachers, transcribed interviews with each teacher participant, lesson observations (for only some of the teachers) and journal notes. The unexpected challenges encountered in finding teachers willing to participate in a sustained professional development initiative are described and critically reflected on and findings in relation to each of the research questions are presented and discussed. A key finding is that societal culture and context fundamentally shaped the inception, development and sustainability of PLCs (Hairon and Dimmock, 2012) at the center of the study. It is argued that many South African teachers’ participation in a PLC is likely to be constrained by their personal and professional life histories and by the passive and compliant identity created for teachers by the lasting effects of the apartheid educational philosophy of fundamental pedagogics and by the currently increasingly prescriptive approach to teaching and assessment adopted by the provincial and national departments of education. Such an identity is likely to impact on teachers’ confidence and sense of agency to devise and drive their own professional growth agenda. The study found that the ethos of the schools in which teachers teach is also likely to be influential in enabling or constraining whether, and if so, how, teachers choose to participate in a PLC. An implication of this finding is that there is a need to acknowledge the impact of contexts on teachers’ attitudes and values, and to structure PLC activities to challenge existing assumptions and create a dissonance that will enable current knowledge to be reconstructed (Nonaka and Takeuchi, 1995). The teachers who participated in the study used similar, traditional approaches to the teaching of writing which involved the presentation of ‘set prescriptions’, with an emphasis on grammatical correctness and the final product rather than on writing as a process of thinking, drafting, reflecting and redrafting. In instances where teachers adopted strongly deficit discourses about learners, they tended to resort to low level drill and skill instruction (Ball and Ellis, 2008). I argue that providing opportunities for teachers to engage thoughtfully and critically on their understanding and enactment of writing pedagogy in their contexts and classrooms over an extended period of time in a PLC could contribute to the disruption of deficit discourses and to the reconstruction of writing pedagogies. Key words: professional learning communities; societal culture; context; teacher life histories; teacher identities; dissonance; deficit discourse; teacher agency; writing pedagogies
A thesis submitted to the Wits School of Education Faculty of Humanities University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2017.
Keywords: Professional learning communities--South Africa--Case studies; English language--Writing--Study and teaching--South Africa; Teachers--Training of--South Africa